2011
DOI: 10.1002/eat.20784
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the application of exposure and response prevention to the treatment of anorexia nervosa

Abstract: Objective Anorexia nervosa (AN) is a life threatening and difficult to treat illness with a high relapse rate. Current treatments are inadequate and new approaches to treatment are needed. Method We review the data on anxiety in AN, the relationship between anxiety disorders and AN, and the use of Exposure and Response Prevention in treatment. Results The overlap between AN and anxiety disorders suggest a model of AN in which baseline anxiety features yield eating related fears, avoidance behaviors, and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
137
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 58 publications
7
137
0
1
Order By: Relevance
“…Second, these findings suggest that theories positing the importance of emotion regulation 4 , as well as those emphasizing anxiety 14,15 , during acute stages of AN are likely both valid, but may be identifying two different processes that may be associated with symptom expression among underweight individuals with AN. The data indicate that in the acute stages of AN, problems appropriately managing emotions may be more highly associated with eating disorder symptoms and impairment for some individuals, while high, but stable levels of anxiety may be more highly associated with eating disorder behavior for others.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, these findings suggest that theories positing the importance of emotion regulation 4 , as well as those emphasizing anxiety 14,15 , during acute stages of AN are likely both valid, but may be identifying two different processes that may be associated with symptom expression among underweight individuals with AN. The data indicate that in the acute stages of AN, problems appropriately managing emotions may be more highly associated with eating disorder symptoms and impairment for some individuals, while high, but stable levels of anxiety may be more highly associated with eating disorder behavior for others.…”
Section: Discussionmentioning
confidence: 94%
“…There is concurrently increasing interest in the role that anxiety plays in influencing AN symptomology 14,15 . It has been suggested that individuals who develop AN have elevated levels of anxiety resulting from a dysfunctional serotonin system, and that restrictive eating serves to reduce baseline levels of anxiety to a more manageable level 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these core diagnostic criteria and the specific behaviors that characterize the two AN subtypes (i.e., binge eating-purging subtype and restricting subtype), many individuals with AN exhibit related behaviors that have been described as compulsive and ritualistic in nature (e.g., Mazure, Halmi, Sunday, Romano, & Einhorn, 1994; Steinglass et al, 2011). One set of body-related ritualistic behaviors that has received attention in the literature is body checking behaviors.…”
mentioning
confidence: 99%
“…They manifest repetitive behaviors (i.e., food rituals) used to decrease anxiety about food, which bear strong similarities to obsessive compulsive disorder (e.g., Hsu, Kaye, & Weltzin, 1993). While there are important differences between eating disorders (EDs) and anxiety disorders, the shared clinical phenomena suggest potentially useful overlap in treatment strategies (Steinglass et al, 2011). …”
mentioning
confidence: 99%